History of the Development of Philosophy and Science in the Islamic Age - Salman Al Farisi Lingga; Salminawati Salminawati; Ahmad Mustaqim; Pandi Kurniawan (Walidem Institute and Publishing, 2023)
The type of research that the author uses is a type of qualitative research using a content analysis approach, or it can be called content research. This analysis is a research technique for making a conclusion or inference that can be replicated and the correctness of the data by taking into account the context. The object of this research is explored through various information in the form of books, interpretations, and journals. This journal aims to discuss Islamic philosophy, born from the holy book of Muslims themselves because it contains many verses that tell people to think. On the other hand, because of the incessant efforts made by Alexander the Great in conquering important cities such as Egypt, Iraq, Syria, and Persia, cultural centres were later established in these important cities which helped develop Alexander's efforts in developing knowledge. Greek knowledge and philosophy.